A Rational Adoption of the High Sensitive Assay for Cardiac Troponin I in Diagnostic Routine. (15th May 2017) - Croce, Antonio; Brunati, Pietro; Colzani, Carlo; Terramocci, Riccardo; Favero, Stefano; Bordoni, Gabriele; Galli, Claudio
Abstract : We describe the adoption of high sensitive troponin I (hsTnI) in clinical practice in two hospital settings in Italy. Samples from 426 consecutive patients (mean age 68.8 ± 17.0) admitted to the Emergency Department with a suspected acute coronary syndrome (ACS) have been tested at admittance and after 3 and 6 hours by contemporary TnI and hsTnI. Results have been compared to the final clinical diagnosis. Troponin was detectable in 68.6% by TnI and 89.9% by hsTnI. Since hsTnI has a lower threshold for females, 38/41 patients with positive values only by hsTnI were women. The correlation between the assays was very high (r = 0.92 ). A diagnosis of acute myocardial infarction (AMI) was made in 45 cases (10.5%). The negative and positive predictive values for a 50% troponin variation at 3 hours were 95.8% and 66.7% for hsTnI and 95.0% and 52.6% for TnI and at 6 hours 90.3% and 100% for hsTnI and 88.9% and 78.9% for TnI, respectively. Receiver operating characteristic (ROC) curve analysis demonstrated a greater efficiency by hsTnI at 3 hours versus 6 hours (AUC = 0.91 versus 0.72). The main benefits of hsTnI are the adoption of gender-specific 99th percentile and the shortening of time to decision.